2015
DOI: 10.18775/ijmsba.1849-5664-5419.2014.29.1001
|View full text |Cite
|
Sign up to set email alerts
|

Does Knowledge Management Lead to Innovation? an Empirical Study on SMEs in Rwanda

Abstract: Abstract:The purpose of this study was to investigate whether knowledge management under its three dimensions of knowledge acquisition, knowledge sharing and responsiveness to knowledge lead to innovation in Rwandan SMEs. The study adopted a cross-sectional survey design to collect data used to examine that relationship. The results revealed that only knowledge sharing was found positive and significant predictor of innovation. This implies that effective knowledge management through knowledge sharing may lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 70 publications
(3 reference statements)
1
2
1
Order By: Relevance
“…The literature also confirms that KM has found a strong and significant relationship between KM and digital financial innovation. The results indicate that KM practices are positively associated with innovation as generally suggested by the KM literature (Zheng, 2005;Jantunen, 2005;Bishop et al, 2008;Byukusenge et al, 2016;Nawab et al, 2015;Kör and Maden, 2013;Nowacki and Bachnik, 2016). This could be attributed to the fact that information technology is used and that there is some form of knowledge being acquired and distributed by commercial banks operating in Lebanon.…”
Section: Digital Financial Innovationsupporting
confidence: 65%
“…The literature also confirms that KM has found a strong and significant relationship between KM and digital financial innovation. The results indicate that KM practices are positively associated with innovation as generally suggested by the KM literature (Zheng, 2005;Jantunen, 2005;Bishop et al, 2008;Byukusenge et al, 2016;Nawab et al, 2015;Kör and Maden, 2013;Nowacki and Bachnik, 2016). This could be attributed to the fact that information technology is used and that there is some form of knowledge being acquired and distributed by commercial banks operating in Lebanon.…”
Section: Digital Financial Innovationsupporting
confidence: 65%
“…The results support the findings of Sulistyo and Siyamtinah (2016) and Battor and Battor (2010) found that the innovation capability affects the improvement of employee performance. The findings do not support the findings of Byukusenge (2016), that finding innovation has no effect on performance improvements.…”
Section: Figure 2 the Results Of Structural Equation Modelcontrasting
confidence: 88%
“…Akram (2017) also found that knowledge sharing has a positive effect on innovation. Knowledge sharing has a significant effect on innovation capability (Kumar and Rose, 2012;Byukusenge et al, 2016). H1: Knowledge sharing significantly affects the innovation capability.…”
Section: Knowledge Sharing and Innovation Capabilitymentioning
confidence: 99%
“…However, for innovation behavior to be effective, it requires support from innovative employees. To foster innovative employees, the implementation of human resource management practices as studied by Nieves & Quintana (2016) is crucial, as it has an impact on business enterprise performance according to Budhwar et al (2007). Based on these insights, we propose the following hypothesis: innovation significantly affects organizational performance.…”
Section: Business Enterprises Performancementioning
confidence: 98%